Predicting try scoring in super 14 rugby union - the development of a superior attacking team scoring system - Lim, E.; Lay, B.; Dawson, B.; Wallman, K.; Anderson, S. (International Journal of Performance Analysis in Sport, 2011)
The aim of this study was to determine if consecutive periods of attacking superiority, as determined by a developed Team Attacking Superiority (TAS) scoring system, could predict try scoring in Super 14 rugby. Game data from 9 games where the Crusaders, Force and Lions played each other in the 2006, 2007 and 2008 competition seasons were analysed. A Player Impact Ranking matrix, developed in an earlier study (Lim et al., 2009), was modified to create a Team Impact Ranking (TIR) matrix. The TIR was then used to calculate the TAS scores to assess consecutive periods of attacking dominance by a team. Results showed that 67% of tries scored resulted from teams maintaining 3 consecutive TAS periods or less. Although the majority of tries scored were from </= 3 consecutive TAS periods, odd ratios revealed that teams were 11.76 times more likely to convert TAS periods into tries scored if they were able to attain 4 or more TAS periods.